Headteachers and Inclusion: Setting the Tone for an Inclusive School - Cláudia Neves; Ana Patrícia Almeida; Marco Ferreira (MDPI AG, 2023)
Inclusion is an unavoidable dimension of education and the school's mission. Educational organisations must therefore seek approaches and practices that materialise in the effective management of diversity, equity and inclusion, since these are conditions for the involvement of the whole community to achieve the goals of education for all. This study sought to answer (i) How do school leaders conceptualize equity and inclusion? (ii) What guidance and administrative procedures do headteachers use to facilitate inclusion? (iii) What characterises their practices concerning leadership for equity and inclusion? The empirical focus of the research was a set of school principals of Portuguese public schools, where a qualitative methodology was used, namely the interview survey technique. The sample gathered 11 interviewees. The results show that, although from an ideological point of view, headteachers have a broad conception of inclusive education, from an operational point of view, the evidence shows the implementation of normative practices. The data point to a reproduction of Portuguese policies and their priorities, showing a leadership engaged in targets, outcomes and performance indicators. The conclusions of the article point to the need to explore new possibilities for understanding inclusion and leadership, and these understandings may impact the school's transformation toward successful inclusion.